Mengungkap Peran Sanksi Adat untuk Mengurangi Potensi Kredit Macet pada Lembaga Perkreditan Desa - Kadek Rina Marlina; Ni Wayan Yulianita Dewi (Universitas Pendidikan Ganesha, 2021)
This research was conducted to determine the role of adat sanctions in reducing the potential for uncollectable loan in the Lembaga Perkreditan Desa Adat Kayuputih Melaka. The uniqueness of this LPD is that it experienced bankruptcy but was able to stand up again by applying adat sanctions. Customary sanctions are used as an internal control system for the Lembaga Perkreditan Desa. This is evidenced by the absence of bad credit figures at the Lembaga Perkreditan Desa Adat Kayuputih Melaka. The method used in this research is a qualitative approach. The type of data used is primary data and secondary data. Data were obtained through interviews with kelian (heads) of the Customary Villages, LPD Chairpersons, LPD Employees, and LPD customer representatives. The reason for choosing these informants is because they are directly related to the rebuilding of the Lembaga Perkreditan Desa. Observations were made on LPD lending, and documentation studies of lending documents and other documents. The data analysis technique used is the interactive data analysis model of Miles and Huberman. The results of this study are that customary sanctions have a very important role in reducing bad credit. This is evidenced by data as of May 2020 showing that there are no customers who experience uncollectable loan.